The Attitudes of Children Undergoing Orthodontic Treatment toward Face Mask Wearing during the COVID-19 Pandemic: A Cross Sectional Study - Jessica Olivia Cherecheș; Gabriela Ciavoi; Abel Emanuel Moca; Raluca Iurcov; Raluca Dima; Marius Bembea; Luminița Ligia Vaida (MDPI AG, 2022)
During the COVID-19 pandemic, the protective face mask has proven to be essential. The protective face masks cover the lower part of the face, including teeth and, for orthodontic patients, the orthodontic appliances. The aim of this study was to assess the impact that the restrictive measures that were imposed during the COVID-19 pandemic and, especially, wearing a protective face mask had on a sample of Romanian children, and to compare the results previously obtained on a sample of Romanian teenagers with the results obtained after investigating children under the age of 12 years. The cross-sectional survey was conducted in two orthodontic offices from the city of Oradea, Romania. The study sample included children with ages between 8 and 11.9 years that were undergoing an orthodontic treatment with removable or fixed orthodontic appliances. After obtaining the results, comparisons were made with the answers provided by a group of adolescents previously investigated. The questionnaires consisted of 9 items that investigated children' attitudes toward protective face mask wearing and other aspects related to the COVID-19 pandemic. Two hundred fifty-six children were included in the study (53.1% female patients, 46.9% male patients). Most of the children were not worried that face masks would hide their orthodontic appliances (Item 1-Never, 40.2%; Rarely, 28.9%) and did not consider that the necessity of face mask wearing negatively impacted their desire to undergo an orthodontic treatment, despite the fact that it covered the appliances (Item 2-Never, 37.1%; Rarely, 31.6%). However, 44.5% of children were not happy because they had to wear a face mask during the orthodontic treatment, considering the fact that it covered the orthodontic appliance (Item 6), and most patients (49.2%) did not want the face mask to continue to be mandatory (Item 7). Although children were not happy that they had to wear a face mask that covered the orthodontic appliances, protective face masks were generally well tolerated by Romanian children.